Online Learning in the Library and Information Science Education During the Covid-19 - Thoriq Tri Prabowo; Nur Riani; Fina Hanifa Hidayati; Heru Sulistya; Lalu Rudy Rustandi (Program Studi Ilmu Perpustakaan UIN Alauddin, 2021)
This study aims to describe the proper online lecture practice during the pandemic Covid-19 in the Department of Library Science of UIN Sunan Kalijaga. This study uses a mixed-method approach (quantitative and qualitative). 92 students as the respondents filled out online questionnaires about their proper online learning. Not only filling in a quantitative questionnaire, these respondents were also given to provide reasons for each filled answer. Online learning in the Department of Library Science of UIN Sunan Kalijaga has been conducted since March 2020. The implementation uses different applications for each lecturer. Some of the most widely used applications are Whatsapp, Google Classroom, eLearning UIN Sunan Kalijaga, online meeting applications such as Zoom, Google Meet, and Webex, Youtube, and podcast applications such as Anchor and Spotify. Evaluation of online learning using the principle of inclusiveness is necessary.